Clarendon News - March 03, 1994 - (:unkn) unknown (My University, 1994)
Microfilm provided by the Panhandle-Plains Historical Museum and Clarendon ISD.
The Clarendon Press changed its name in January 1990 to its original 1878 title, the Clarendon News. The newspaper would be published under this title for several years until it changed names again to the Clarendon Enterprise.
Keywords: Clarendon News.; Clarendon (Tex.)--Newspapers.; Donley County (Tex.)--Newspapers.